Fluorescent glass ceramic with high optical uniformity, preparation method thereof and LED lamp
By using specific types of phosphors and diffusion powders in fluorescent glass ceramics and using sintering and post-treatment technologies, the problem of insufficient optical uniformity of existing fluorescent glass ceramics is solved, and high light efficiency and optical uniformity are achieved.
Patent Information
- Application Number
- CN202411994223.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The optical uniformity of existing fluorescent glass ceramics in LED lamps is insufficient, resulting in uneven distribution of light intensity, spots and dark areas, affecting the visual effect and light effect.
Fluorescent glass ceramics including glass powder, phosphor and diffusion powder are used. The diffusion powder is selected from silicon dioxide, alumina and boron nitride. The types of phosphors include (Ca, Sr, Ba) SiON:Eu2+, etc. Through sintering and post-treatment technology, the uniformity of the material and the efficient scattering effect are ensured.
It significantly improves optical uniformity, and the CoA value does not exceed 0.035, reducing light spots and dark zone phenomena, providing a more uniform and consistent lighting effect while maintaining high light efficiency.
Smart Images

Figure BDA0005224252760000111 
Figure BDA0005224252760000121
Abstract
Description
Technical Field
[0001] This application belongs to the field of semiconductor lighting technology, specifically relating to a fluorescent glass ceramic with high optical uniformity, its preparation method, and an LED lamp. Background Technology
[0002] With the increasing demand for efficient and environmentally friendly lighting technologies in modern society, light-emitting diodes (LEDs) have become a research and application hotspot due to their advantages such as high luminous efficacy, long lifespan, and low energy consumption, gradually replacing traditional incandescent and fluorescent lamps. To further improve the performance of LED lamps, fluorescent glass ceramics, as a high-performance fluorescent material, have received widespread attention due to their excellent optical properties and stability.
[0003] Fluorescent glass-ceramics are a special material that combines the advantages of glass and ceramics. They possess excellent thermal and chemical stability, superior mechanical properties, and outstanding luminescent performance. This material emits light under illumination of specific wavelengths and is widely used in lighting, displays, decoration, and many other fields. Particularly in LED lights, the application of fluorescent glass-ceramics can significantly improve luminous efficacy and color rendering, enhance thermal stability, and extend the lifespan of LED lights.
[0004] However, despite the achievements of existing fluorescent glass ceramics in LED lights, significant shortcomings remain in terms of optical uniformity. Existing fluorescent glass ceramics exhibit uneven light intensity distribution in different directions, easily resulting in noticeable bright spots and dark areas. This not only affects the visual effect of LED lights but may also lead to wasted light energy and reduced overall luminous efficacy. Furthermore, differences in light color may occur in different areas, resulting in color inhomogeneity and impacting the lighting effect.
[0005] To improve optical uniformity, a common method is to reduce the particle size of the phosphor. While this method can improve optical uniformity to some extent, it leads to a decrease in luminous efficacy. The defects in optical uniformity of fluorescent glass ceramics not only affect the visual effect of LED lights but also limit their development in certain application areas.
[0006] Therefore, there is an urgent need to develop a fluorescent glass-ceramic with good optical uniformity, which can significantly improve optical uniformity while maintaining high luminous efficiency, thereby meeting the market demand for efficient, uniform, and environmentally friendly lighting technology. Summary of the Invention
[0007] In view of this, this application provides a fluorescent glass-ceramic with high optical uniformity, a method for preparing the same, and an LED lamp. The fluorescent glass-ceramic of this application can significantly improve optical uniformity while maintaining high luminous efficacy. LEDs packaged using this fluorescent glass-ceramic have a CoA value (angular distribution coefficient) of no more than 0.035.
[0008] In a first aspect, this application provides a fluorescent glass-ceramic with high optical uniformity, comprising glass powder, phosphor, and diffusing powder;
[0009] The diffusion powder is selected from at least one of silicon dioxide, aluminum oxide and boron nitride;
[0010] The phosphor comprises (Ca,Sr,Ba)SiON:Eu 2+ β-Sialon:Eu 2+ AlON:Mn 2+ (Lu,Y,Gd)3(Al,Ga)5O 12 :Ce 3+ α-SiAlON:Eu 2+ (Ca,Sr)AlSiN3:Eu 2+ and (Ca,Sr,Ba)2Si5N8:Eu 2+ At least one of them;
[0011] The glass powder content is 40-90% by mass percentage, the phosphor content is 5-55%, and the diffuser content is 5-30%.
[0012] By adopting the above technical solution, the fluorescent glass-ceramic of this application maintains high luminous efficiency while significantly improving optical uniformity. In the fluorescent glass-ceramic of this application, glass powder serves as the matrix material, providing the necessary mechanical strength and supporting structure, while also acting as a carrier for the phosphor and diffusing powder. The phosphor is responsible for converting incident light into the desired output spectrum and is a key factor determining the final light color. The phosphors selected in this application are stable at high temperatures, do not react with the glass matrix during high-temperature fusion, and can maintain high luminous efficiency while efficiently converting light. An appropriate amount of phosphor ensures sufficient luminous intensity without reducing transmittance or causing aggregation problems due to excessive amounts. The diffusing powder has different refractive indices. When light passes through the glass-ceramic containing these powders, the light path is changed due to interface effects and refractive index differences, thereby achieving the effect of scattering light and realizing efficient scattering and light homogenization, which helps to improve optical uniformity. The selection and proportion of diffusing powder in this application ensures uniform propagation of light in the material and reduces light spots and dark areas. If there is too little diffusing powder, there will be few scattering sources, which may not be able to scatter light sufficiently, resulting in poor light uniformity. If there is too much diffusing powder, it may reduce the transparency of the fluorescent glass and reduce the light efficiency.
[0013] Optionally, the glass powder is silicate glass powder; the molar percentage content of the raw materials of the silicate glass powder is: SiO2: 40-70%, B2O3: 5%-30%, RO: 2%-20%, R2O: 0.1%-15%;
[0014] Wherein, RO is selected from at least one of MgO, CaO, SrO, and BaO;
[0015] The R2O is selected from at least one of Li2O, Na2O, and K2O.
[0016] By employing the above technical solutions, silicate glass exhibits high transparency, effectively conducting light and ensuring that light emitted by phosphors can pass through smoothly. It also possesses excellent thermal and chemical stability. By adjusting the component ratios, its compatibility with phosphors and diffusing powders can be optimized, thereby improving optical performance.
[0017] Optionally, by mass percentage, the content of the glass powder is 42-85%, the content of the phosphor is 7-50%, and the content of the diffusing powder is 8-25%.
[0018] Optionally, the diffusion powder is selected from at least two of silicon dioxide, aluminum oxide, and boron nitride.
[0019] By employing the above technical solution, using at least two of silica, alumina, and boron nitride as diffusing powders, the scattering effect can be optimized. Different types of diffusing powders, due to their varying refractive indices, particle sizes, and shapes, can influence the light path at multiple scales, thereby more effectively dispersing light, improving light uniformity, and reducing light spots and dark areas.
[0020] Optionally, the diffusion powder satisfies at least one of the following conditions:
[0021] (1) Based on the mass of the diffusion powder, the mass content of the silica is 8-24%;
[0022] (2) Based on the mass of the diffusion powder, the mass content of the alumina is 1-20%;
[0023] (3) Based on the mass of the diffuser powder, the mass content of the boron nitride is 1-5%.
[0024] By employing the above technical solutions, the mass content range of the diffusing powder can optimize optical performance. By controlling the proportion of each diffusing powder, the scattering path of light can be optimized at different scales, thereby achieving a more uniform light distribution and helping to reduce light spots and dark areas. An appropriate combination of diffusing powders can also minimize light energy absorption while ensuring efficient scattering, maintaining high luminous efficacy.
[0025] Optionally, the particle size D50 of the diffusion powder is 0.5 to 10 μm.
[0026] By adopting the above technical solution, the particle size range of the diffuser powder in this application can effectively scatter light without excessive absorption or reflection, thereby achieving a uniform light distribution. An appropriate particle size helps maintain high transmittance, ensuring that most incident light can be effectively converted and pass through the material, maintaining high luminous efficiency. If the particle size of the diffuser powder is too large, it may lead to a decrease in scattering efficiency, failing to adequately change the light path, resulting in direct light or reflection, producing obvious light spots and dark areas. If the particle size of the diffuser powder is too small, it may increase light absorption and scattering losses, leading to a decrease in luminous efficiency.
[0027] Optionally, the particle size D50 of the diffusion powder is 2 to 6 μm.
[0028] Secondly, this application provides a method for preparing the above-mentioned fluorescent glass ceramic, comprising the following steps:
[0029] Step S1: Mix the glass powder, phosphor powder and diffusion powder, press them into shape, and obtain a green body;
[0030] Step S2: Sinter the green body in air atmosphere to obtain a fluorescent glass-ceramic ingot;
[0031] Step S3: The fluorescent glass-ceramic ingot is sliced, ground, and polished to obtain fluorescent glass-ceramic.
[0032] By adopting the above technical solution, the preparation method of this application is simple and controllable, ensuring the uniform distribution of phosphor and diffusing powder in the glass matrix, achieving excellent optical uniformity. The sintering conditions and post-treatment process ensure that the luminous efficiency of the phosphor is not impaired, while reducing unnecessary light loss. Sintering in an air atmosphere helps to remove volatile impurities and prevent adverse chemical reactions, ensuring the stability of the material.
[0033] Optionally, the preparation method satisfies at least one of the following conditions:
[0034] (1) In step S1, the thickness of the green blank is 1 to 40 mm;
[0035] (2) In step S2, the sintering temperature is 550-850℃ and the sintering time is 10-120min;
[0036] (3) In step S3, the thickness of the fluorescent glass ceramic is 0.1 to 0.3 mm.
[0037] By adopting the above technical solutions, the appropriate green body thickness helps to ensure that heat can be transferred evenly during sintering, avoiding local overheating or uneven cooling, thereby ensuring the consistency of the internal structure of the material and the uniformity of its optical properties.
[0038] The sintering temperature of this application allows for a more compact bonding between the glass matrix, phosphor, and diffusing powder in the fluorescent glass-ceramic, resulting in optimal luminescence efficiency during subsequent use. Sufficient sintering time allows for the complete removal of air bubbles from the fluorescent glass-ceramic, forming a stable and dense microstructure. It also helps release internal stress, preventing cracks or other defects during later use.
[0039] The thickness of the fluorescent glass-ceramic in this application ensures uniform light propagation within the material while maintaining high luminous efficacy, reducing light spots and dark areas. Excessive thickness may increase the optical path length, leading to greater light loss and scattering, and ultimately reducing luminous efficacy.
[0040] Thirdly, this application provides an LED lamp, including the above-mentioned fluorescent glass ceramic and an optical power substrate; the fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
[0041] By adopting the above technical solution, the LED lamp of this application uses a fluorescent glass ceramic sheet with high optical uniformity, which ensures the uniform distribution of light in all directions, reduces light spots and dark areas, and provides a more uniform and consistent lighting effect.
[0042] In summary, the present invention has at least one of the following beneficial technical effects:
[0043] 1. The fluorescent glass-ceramic of this application can maintain high luminous efficiency and significantly improve optical uniformity.
[0044] 2. The diffusing powder of this application is uniformly distributed in the fluorescent glass. When light passes through it, the path of the light is changed due to the interface effect and the difference in refractive index, which achieves efficient scattering and light homogenization effect and improves optical uniformity.
[0045] 3. The preparation method of this application is simple and controllable, ensuring the uniform distribution of phosphor and diffusing powder in the glass substrate and achieving excellent optical uniformity.
[0046] 4. The LED lamp of this application uses a fluorescent glass-ceramic sheet with high optical uniformity, which ensures uniform distribution of light in all directions, reduces light spots and dark areas, and provides a more uniform and consistent lighting effect. Detailed Implementation
[0047] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0048] The inventors of this application discovered in their research on fluorescent glass ceramics that existing fluorescent glass ceramics have significant defects in optical uniformity. The light intensity distribution is uneven in different directions, easily resulting in noticeable light spots and dark areas. Furthermore, the color of light may differ in different areas, leading to color inhomogeneity and affecting the lighting effect.
[0049] To address the aforementioned issues, this application proposes a fluorescent glass-ceramic with high optical uniformity, comprising glass powder, phosphor, and diffusing powder;
[0050] The diffusion powder is selected from at least one of silicon dioxide, aluminum oxide and boron nitride;
[0051] The phosphor comprises (Ca,Sr,Ba)SiON:Eu 2+ β-Sialon:Eu 2+ AlON:Mn 2+ (Lu,Y,Gd)3(Al,Ga)5O 12 :Ce 3+ α-SiAlON:Eu 2+ (Ca,Sr)AlSiN3:Eu 2+ and (Ca,Sr,Ba)2Si5N8:Eu 2+ At least one of them;
[0052] The glass powder content is 40-90% by mass percentage, the phosphor content is 5-55%, and the diffuser content is 5-30%.
[0053] The preparation method includes the following steps:
[0054] Step S1: Mix the glass powder, phosphor powder and diffusion powder, press them into shape, and obtain a green body;
[0055] Step S2: Sinter the green body in air atmosphere to obtain a fluorescent glass-ceramic ingot;
[0056] Step S3: The fluorescent glass-ceramic ingot is sliced, ground, and polished to obtain fluorescent glass-ceramic.
[0057] This application also provides an LED lamp, including the above-mentioned fluorescent glass ceramic and an optical power substrate; the fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
[0058] The solution of this application will be described below with reference to the following specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from commercially available products, and the devices or equipment used are all purchased from conventional market sales channels. Specific Implementation
[0060] Example 1
[0061] This embodiment provides a fluorescent glass-ceramic with high optical uniformity, comprising glass powder, phosphor, and diffusing powder; by mass percentage, the content of glass powder is 90%, the content of phosphor is 5%, and the content of diffusing powder is 5%.
[0062] The diffusing powder is silica with a particle size D50 of 0.5 μm; the phosphor is (Lu,Y,Gd)3(Al,Ga)5O. 12 :Ce 3+ ;
[0063] The glass powder is silicate glass powder, and the molar percentage of the raw materials of silicate glass powder is: SiO2: 55%, B2O3: 17%, MgO: 11%, Li2O: 7%;
[0064] The preparation method includes the following steps:
[0065] Step S1: Mix glass powder, phosphor powder and diffusion powder, press and shape to obtain a green body with a thickness of 20mm;
[0066] Step S2: Sinter the green body in air atmosphere at a temperature of 650℃ for 120 minutes to obtain a fluorescent glass ceramic ingot.
[0067] Step S3: The fluorescent glass ceramic ingot is sliced, ground, and polished to obtain fluorescent glass ceramic with a thickness of 0.2 mm.
[0068] This embodiment also provides an LED lamp, including the above-mentioned fluorescent glass ceramic and an optical power substrate; the fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
[0069] Example 2
[0070] This embodiment provides a fluorescent glass-ceramic with high optical uniformity, comprising glass powder, phosphor, and diffusing powder; by mass percentage, the content of glass powder is 42%, the content of phosphor is 50%, and the content of diffusing powder is 8%.
[0071] The diffusing powder is silica with a particle size D50 of 0.5 μm; the phosphor is (Lu,Y,Gd)3(Al,Ga)5O. 12 :Ce 3+ ;
[0072] The glass powder is silicate glass powder, and the molar percentage of the raw materials of silicate glass powder is: SiO2: 55%, B2O3: 17%, MgO: 11%, Li2O: 7%;
[0073] The preparation method includes the following steps:
[0074] Step S1: Mix glass powder, phosphor powder and diffusion powder, press and shape to obtain a green body with a thickness of 20mm;
[0075] Step S2: Sinter the green body in air atmosphere at a temperature of 650℃ for 120 minutes to obtain a fluorescent glass ceramic ingot.
[0076] Step S3: The fluorescent glass ceramic ingot is sliced, ground, and polished to obtain fluorescent glass ceramic with a thickness of 0.2 mm.
[0077] This embodiment also provides an LED lamp, including the above-mentioned fluorescent glass ceramic and an optical power substrate; the fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
[0078] Example 3
[0079] This embodiment provides a fluorescent glass-ceramic with high optical uniformity, comprising glass powder, phosphor, and diffusing powder; by mass percentage, the content of glass powder is 68%, the content of phosphor is 7%, and the content of diffusing powder is 25%.
[0080] The diffusing powder is silica with a particle size D50 of 0.5 μm; the phosphor is (Lu,Y,Gd)3(Al,Ga)5O. 12 :Ce 3+ ;
[0081] The glass powder is silicate glass powder, and the molar percentage of the raw materials of silicate glass powder is: SiO2: 55%, B2O3: 17%, MgO: 11%, Li2O: 7%;
[0082] The preparation method includes the following steps:
[0083] Step S1: Mix glass powder, phosphor powder and diffusion powder, press and shape to obtain a green body with a thickness of 20mm;
[0084] Step S2: Sinter the green body in air atmosphere at a temperature of 650℃ for 120 minutes to obtain a fluorescent glass ceramic ingot.
[0085] Step S3: The fluorescent glass ceramic ingot is sliced, ground, and polished to obtain fluorescent glass ceramic with a thickness of 0.2 mm.
[0086] This embodiment also provides an LED lamp, including the above-mentioned fluorescent glass ceramic and an optical power substrate; the fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
[0087] Example 4
[0088] This embodiment provides a fluorescent glass-ceramic with high optical uniformity, comprising glass powder, phosphor, and diffusing powder; by mass percentage, the content of glass powder is 65%, the content of phosphor is 5%, and the content of diffusing powder is 30%.
[0089] The diffusing powder is silica with a particle size D50 of 0.5 μm; the phosphor is (Lu,Y,Gd)3(Al,Ga)5O. 12 :Ce 3+ ;
[0090] The glass powder is silicate glass powder, and the molar percentage of the raw materials of silicate glass powder is: SiO2: 55%, B2O3: 17%, MgO: 11%, Li2O: 7%;
[0091] The preparation method includes the following steps:
[0092] Step S1: Mix glass powder, phosphor powder and diffusion powder, press and shape to obtain a green body with a thickness of 20mm;
[0093] Step S2: Sinter the green body in air atmosphere at a temperature of 650℃ for 120 minutes to obtain a fluorescent glass ceramic ingot.
[0094] Step S3: The fluorescent glass ceramic ingot is sliced, ground, and polished to obtain fluorescent glass ceramic with a thickness of 0.2 mm.
[0095] This embodiment also provides an LED lamp, including the above-mentioned fluorescent glass ceramic and an optical power substrate; the fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
[0096] Example 5
[0097] This embodiment provides a fluorescent glass-ceramic with high optical uniformity, comprising glass powder, phosphor, and diffusing powder; by mass percentage, the content of glass powder is 65%, the content of phosphor is 18%, and the content of diffusing powder is 17%.
[0098] The diffusing powder is silica with a particle size D50 of 0.5 μm; the phosphor is (Lu,Y,Gd)3(Al,Ga)5O. 12 :Ce 3+ ;
[0099] The glass powder is silicate glass powder, and the molar percentage of the raw materials of silicate glass powder is: SiO2: 55%, B2O3: 17%, MgO: 11%, Li2O: 7%;
[0100] The preparation method includes the following steps:
[0101] Step S1: Mix glass powder, phosphor powder and diffusion powder, press and shape to obtain a green body with a thickness of 20mm;
[0102] Step S2: Sinter the green body in air atmosphere at a temperature of 650℃ for 120 minutes to obtain a fluorescent glass ceramic ingot.
[0103] Step S3: The fluorescent glass ceramic ingot is sliced, ground, and polished to obtain fluorescent glass ceramic with a thickness of 0.2 mm.
[0104] This embodiment also provides an LED lamp, including the above-mentioned fluorescent glass ceramic and an optical power substrate; the fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
[0105] Comparative Example 1
[0106] The difference between Comparative Example 1 and Example 5 is that Comparative Example 1 does not contain diffusing powder, the content of glass powder is 65%, and the content of phosphor is 35%.
[0107] Comparative Example 2
[0108] The difference between Comparative Example 2 and Example 5 is that in Comparative Example 2, the diffusing powder silicon dioxide was replaced with an equal amount of aluminum nitride.
[0109] Experimental testing
[0110] Testing items and testing methods
[0111] CoA (Coefficient of Angular Distribution): This is an indicator used to measure the uniformity of light intensity distribution of a light source in different directions. Specifically, the CoA value is the difference between the color coordinate y at an angle of 0° (perpendicular to the LED) and the color coordinate y at an angle of 80°. Therefore, the smaller the CoA value, the more uniform the light intensity distribution of the light source in all directions.
[0112] CoA value detection method: The prepared fluorescent glass ceramic is cut to obtain a fluorescent glass ceramic sheet with a length × width of 1mm × 1mm. This sheet is then used as a fluorescent conversion material to encapsulate an LED bead and soldered onto a substrate. The bead is placed on a test fixture and lit. The entire semicircle of the LED radiation direction is measured using a variable angle photometer (LEDGON 100) from IS GmbH, Germany. The color coordinate parameters that change with the angle are measured, and the CoA value is calculated.
[0113] Luminous efficiency: The luminous efficiency of an LED is the ratio of the luminous flux (lm) emitted by the LED after it is lit to its lighting power (W), which is used to measure the photoelectric conversion efficiency of a light source.
[0114] Luminous efficiency testing method: Place the LED beads soldered on the substrate on the test fixture, insert the integrating sphere, and light them up. Use a HAAS-2000 rapid spectroradiometer to analyze and test the luminous efficiency of the LED beads.
[0115] The luminous efficiency and CoA value of the LEDs obtained by encapsulating fluorescent glass ceramics in Examples 1-5 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1.
[0116] Table 1
[0117]
[0118]
[0119] As shown in Table 1, the LED lamps encapsulated in fluorescent glass ceramics prepared in Examples 1-5 of this application exhibit high luminous efficiency, a CoA value ≤ 0.035, and no visible yellow spots. Therefore, the fluorescent glass ceramics prepared in this application can significantly improve optical uniformity while maintaining high luminous efficiency.
[0120] Comparative Example 1, which does not contain diffuser powder, shows a significantly higher CoA value and worse optical uniformity in the LED lamp obtained by the fluorescent glass-ceramic encapsulation.
[0121] In Comparative Example 2, replacing the diffusing powder silicon dioxide with an equal amount of aluminum nitride resulted in a significant decrease in the luminous efficiency of the LED lamp encapsulated in a fluorescent glass ceramic, while the CoA value increased. It is speculated that the aluminum nitride powder reacts with the oxides in the glass matrix during high-temperature sintering, reducing the density and transparency of the fluorescent glass, thus affecting the luminous efficiency.
[0122] Examples 6-20
[0123] Example 6
[0124] The difference between Example 6 and Example 5 is that the phosphor in Example 6 is (Ca,Sr,Ba)2Si5N8:Eu. 2+ .
[0125] Example 7
[0126] The difference between Example 7 and Example 5 is that the diffusion powder in Example 7 is alumina.
[0127] Example 8
[0128] The difference between Example 8 and Example 5 is that the diffusion powder in Example 8 is silicon dioxide and aluminum oxide, and the mass content of silicon dioxide is 16% based on the mass of the diffusion powder.
[0129] Example 9
[0130] The difference between Example 9 and Example 5 is that the diffusion powder in Example 9 is alumina and boron nitride, and the mass content of alumina is 10% based on the mass of the diffusion powder.
[0131] Example 10
[0132] The difference between Example 10 and Example 5 is that the diffusion powder in Example 10 is boron nitride and silicon dioxide, and the mass content of boron nitride is 3% based on the mass of the diffusion powder.
[0133] Example 11
[0134] The difference between Example 11 and Example 8 is that in Example 11, the particle size D50 of the diffusion powder is 2 μm.
[0135] Example 12
[0136] The difference between Example 12 and Example 8 is that in Example 12, the particle size D50 of the diffusion powder is 4 μm.
[0137] Example 13
[0138] The difference between Example 13 and Example 8 is that in Example 13, the particle size D50 of the diffusion powder is 6 μm.
[0139] Example 14
[0140] The difference between Example 14 and Example 8 is that in Example 14, the particle size D50 of the diffusion powder is 10 μm.
[0141] Example 15
[0142] The difference between Example 15 and Example 12 is that in step S1 of the preparation method of Example 15, the thickness of the green blank is 1 mm.
[0143] Example 16
[0144] The difference between Example 16 and Example 12 is that in step S1 of the preparation method of Example 16, the thickness of the green blank is 40 mm.
[0145] Example 17
[0146] The difference between Example 17 and Example 12 is that in step S2 of the preparation method in Example 17, the sintering temperature is 700°C and the sintering time is 65 min.
[0147] Example 18
[0148] The difference between Example 18 and Example 12 is that in step S2 of the preparation method in Example 18, the sintering temperature is 850°C and the sintering time is 10 min.
[0149] Example 19
[0150] The difference between Example 19 and Example 17 is that in step S3 of the preparation method in Example 19, the thickness of the fluorescent glass ceramic is 0.1 mm.
[0151] Example 20
[0152] The difference between Example 20 and Example 17 is that in step S3 of the preparation method in Example 20, the thickness of the fluorescent glass ceramic is 0.3 mm.
[0153] The luminous efficiency and CoA value of the LED lamps obtained by encapsulating the fluorescent glass ceramics prepared in Examples 6 to 20 were tested, and the test results are shown in Table 2.
[0154] Table 2
[0155] Luminous efficacy (lm / W) CoA value Example 6 98 0.030 Example 7 140 0.031 Example 8 138 0.027 Example 9 138 0.028 Example 10 138 0.028 Example 11 139 0.027 Example 12 140 0.025 Example 13 140 0.026 Example 14 139 0.028 Example 15 140 0.027 Example 16 140 0.028 Example 17 141 0.024 Example 18 140 0.026 Example 19 141 0.026 Example 20 139 0.027
[0156] As can be seen from the test results in Table 2, the difference between Example 6 and Example 5 is that the choice of phosphor is different, and the luminous efficiency of the LED lamp obtained by the fluorescent glass-ceramic encapsulation is different.
[0157] The difference between Examples 7-10 and Example 5 lies in the selection of the diffuser powder. Among them, the LED lamp obtained by the fluorescent glass-ceramic encapsulation prepared in Example 8 has the lowest CoA value and the best optical uniformity.
[0158] The difference between Examples 11-14 and Example 8 is that the particle size of the diffuser powder is different. Among them, the LED lamp obtained by the fluorescent glass-ceramic encapsulation prepared in Example 12 has the lowest CoA value while maintaining high luminous efficacy.
[0159] The difference between Examples 15 and 16 and Example 12 is that the thickness of the green blank is different. Among them, the LED lamp obtained by the fluorescent glass-ceramic encapsulation prepared in Example 12 has the lowest CoA value.
[0160] The difference between Examples 17 and 18 and Example 12 is that the sintering temperature and sintering time are different. Among them, the LED lamp obtained by the fluorescent glass-ceramic encapsulation prepared in Example 17 has the highest luminous efficiency and the lowest CoA value.
[0161] The difference between Examples 19, 20 and 17 is that the thickness of the fluorescent glass ceramic is different. Among them, the LED lamp encapsulated with the fluorescent glass ceramic prepared in Example 17 can maintain high luminous efficacy while having the lowest CoA value.
[0162] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the principles of this application should be included within the protection scope of this application.
Claims
1. A fluorescent glass ceramic with high optical uniformity, characterized in that: Including glass powder, phosphor powder and diffusion powder; The diffusion powder is selected from at least one of silicon dioxide, aluminum oxide and boron nitride; The phosphor includes (Ca, Sr, Ba)SiON:Eu 2+ ,β-Sialon:Eu 2+ 、AlON:Mn 2+ 、(Lu,Y,Gd)3(Al,Ga)5O 12 :Ce 3+ 、α-SiAlON:Eu 2+ 、(Ca,Sr)AlSiN3:Eu 2+ and (Ca,Sr,Ba)2Si5N8:Eu 2+ At least one of; In terms of mass percentage, the content of the glass powder is 40-90%, the content of the fluorescent powder is 5-55%, and the content of the diffusion powder is 5-30%.
2. The fluorescent glass ceramic according to claim 1, characterized in that: The glass powder is silicate glass powder; the molar percentage of the raw materials of the silicate glass powder is: SiO2: 40-70%, B2O3: 5%-30%, RO: 2%-20%, R2O: 0.1%-15%; Wherein, the RO is selected from at least one of MgO, CaO, SrO and BaO; The R2O is selected from at least one of Li2O, Na2O, and K2O.
3. The fluorescent glass ceramic according to claim 1, characterized in that: In terms of mass percentage, the content of the glass powder is 42-85%, the content of the fluorescent powder is 7-50%, and the content of the diffusion powder is 8-25%.
4. The fluorescent glass ceramic according to any one of claims 1 to 3, characterized in that: The diffusion powder is selected from at least two of silicon dioxide, aluminum oxide and boron nitride.
5. The fluorescent glass ceramic according to claim 4, characterized in that: The diffusion powder satisfies at least one of the following conditions: (1) Based on the mass of the diffusion powder, the mass content of the silicon dioxide is 8 to 24%; (2) Based on the mass of the diffusion powder, the mass content of the aluminum oxide is 1 to 20%; (3) Based on the mass of the diffusion powder, the mass content of the boron nitride is 1-5%.
6. The fluorescent glass ceramic according to claim 5, characterized in that: The particle size D50 of the diffusion powder is 0.5-10 μm.
7. The fluorescent glass ceramic according to claim 6, characterized in that: The particle size D50 of the diffusion powder is 2-6 μm.
8. A method for preparing the fluorescent glass ceramic according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1: mixing the glass powder, phosphor powder and diffusion powder, and pressing and molding them to obtain a green body; Step S2: sintering the green body in an air atmosphere to obtain a fluorescent glass ceramic ingot; Step S3: Slicing, grinding and polishing the fluorescent glass ceramic ingot to obtain fluorescent glass ceramic.
9. The preparation method according to claim 8, characterized in that: The preparation method satisfies at least one of the following conditions: (1) In step S1, the thickness of the green body is 1 to 40 mm; (2) In step S2, the sintering temperature is 550-850° C. and the sintering time is 10-120 min; (3) In step S3, the thickness of the fluorescent glass ceramic obtained is 0.1 to 0.3 mm.
10. An LED lamp, characterized in that: It comprises the fluorescent glass ceramics as described in any one of claims 1 to 7, and an optical power substrate; the fluorescent glass ceramics are cut to obtain a fluorescent glass ceramic sheet with a length×width of 1mm×1mm, and the fluorescent glass ceramic sheet is attached to the light-emitting surface of the optical power substrate.
Citation Information
Patent Citations
Glass ceramic body, laminate, housing for portable electronic equipment, and portable electronic equipment
CN104169239A
Aluminoborosilicate YAG glass ceramic and preparation method thereof
CN104529168A
Fluorescence conversion device for realizing high-quality warm white laser illumination light source
CN113251326A
Laser fluorescent material, preparation method and application
CN113528138A
Wavelength conversion member and light emitting device using same
CN115172566A